Surgery, anesthesia, and pathology: A practical primer on greening the delivery of surgical care - Sofya H. Asfaw; Ursula Galway; Tara Hata; Julie Moyle; Ilyssa O. Gordon (Elsevier, 2021)
Because of its energy intensive requirements and multi-disciplinary interdependencies, perioperative care, including surgery, anesthesia, and pathology, is one of the greatest contributors to the direct greenhouse gas emissions of healthcare systems. By reducing this contribution, the paradox of harming human health through the delivery of healthcare services can be addressed. Energy use and waste generation are the main underlying factors contributing to these downstream health harms of providing surgical care. On-site energy is consumed primarily by heating ventilation and air conditioning systems, lighting, and equipment. A variety of different types of waste are also generated on-site, including regulated medical waste, healthcare plastic and packaging waste, single-use devices, anesthetic gasses, medication, chemicals, and water. In this review, we discuss practical ways to reduce direct energy use and decrease and avoid waste generation during the surgical experience. Following these environmental best practices supports triple bottom line performance, which delivers significant financial, environmental, and social benefits.